Response to complexity: survivors of domestic abuse with “complex needs”: research summary report for Nottinghamshire Office of Police and Crime Commissioners’ Women’s Safety Reference Group - Harris, Lyndsey (University of Nottingham, 2018)
This report was presented to the Safety for Women Reference Group of The Nottinghamshire Office of Police and Crime Commissioner. The report summarises the author’s body of research exploring the experience of survivors of domestic abuse accessing service provision who have been categorised as having "complex needs" and ‘multiple disadvantage’. A critical discussion of the terminology "complex needs" is presented. The report highlights that there remains no consensus in defining what is meant by “complex needs”. This mainly relates to the diversity of needs and the intersectionality of issues that can result in a survivor’s experience being considered complex. Nationally funded projects addressing ‘complex needs’ include efforts to improve support for survivors who have two or more needs (of which domestic abuse might be one) in a variety of contexts including, for example: specialist ‘complex needs’ refuge provision; funding of specialist support workers (often centred on one particular need identified as being required locally e.g. mental health, substance misuse, legal advice); programmes of support within Women’s Centres. The emphasis has been on engaging survivors with services to provide additional support. The report encourages practitioners to think about “complex needs” in terms of the complexity service providers can experience when working with survivors with multiple disadvantage. It highlights that ‘multiple disadvantage’ terminology captures the number of things which are working against a survivor. ‘Complex needs’ encapsulates and emphasizes the responsibility on commissioners, service providers and multi-agency partnerships to recognize how their services might facilitate a person centred approach to address any wider barriers to essential services. It is recognised this is a difficult task (is complex) for service providers, as service provision in one area may unintentionally have a negative impact upon the survivor in other areas of their life. The report then presents the latest data from the Response to Complexity (R2C) project (Phase 2). Sections 4-6 of the report summarise the author’s evidence submission, in February 2018, to The Commission Looking at the Needs of Vulnerable Women who have Suffered from Neglect and Abuse, chaired by Baroness Hilary Armstrong, which discusses what is working well and what needs to be improved for survivors of domestic abuse with multiple disadvantage.